A vidéki területek ellenálló képességének javítása okos megoldások segítségével - Péter Zsolt; Orosz Dániel (Egyesület Közép-Európa Kutatására, Szegedi Tudományegyetem Juhász Gyula Pedagógusképző Kar Szeged, 2020)
Territorial development is increasingly demanding the use of advanced technologies as growing number of tasks must be solved. While the main challenges in cities are to improve the quality of life of a large number of people and to solve increasingly complex tasks, in rural areas – in many cases – the unstoppable aging, the emigration of young people and the degradation of services are the most important challenges. Basic IT infrastructures have already been developed in most rural areas (eg broadband Internet access), and the cost of home-based devices has fallen to a fraction compared with decades ago, so these are relatively easy to access for everyone. Unfortunately, the existence of "hardware" is often accompanied by a lack of proper "software" and knowledge. In our opinion, one of the potential outbreaks of rural areas is the widespread use of some smart solutions already developed in cities but with the necessary modifications. In our study we examine the current situation of the "smart solutions" in rural areas, and in which extent those solutions can contribute to the resilience of rural areas.
Keywords: Társadalomtudományok; Társadalom- és gazdaságföldrajz